Study of the sorption properties of solvents in thinlayer and column chromatography - Vu Ngoc Dan; V. F. Novikov (Известия высших учебных заведений: Проблемы энергетики)
Much attention is paid to the consideration of the causes of transformer oil aging under the influence of technogenic and natural factors. The paper insulation destruction mechanism is considered, as a result of which furan compounds are formed that enter the transformer oil and worsen its dielectric characteristics. The characteristics of the domestic transformer oil grade GK-1 obtained using the technology of hydrocracking in a hydrogen medium are given. Furan compounds are formed in used transformer oil, which are monitored using chromatographic analysis methods according to standard procedures. The group composition of transformer oil was determined using thin layer chromatography. As a solvent used n. Hexane. To extract furan compounds from transformer oil, various organic solvents are used, the physicochemical properties of which are given in this work. It was found that the retention time of the studied sorbates corresponds to an increase in their boiling points for ethyl acetate, methyl ethyl ketone and dodecane. In the case of isopropanol, which has a close boiling point with ethyl acetate and methyl ethyl ketone, a significant increase in retention time is observed, which is associated with the formation of an intermolecular hydrogen bond. The dependence of the spot diameter of furan substances on their concentration was established under conditions of thin-layer chromatography on Sorbfil plastics. Moreover, the most effective separation is characteristic of furfural. In this case, the chromatographic spots are small in size with good fidelity. The ascending mode of column liquid chromatography was used to determine the dependence of the retention time of standard sorbates on the length of the Silyochrome S-80 sorption layer, which is parabolic. It was found that the highest retention times are characteristic of ethoxyethanol and isopropanol, which is consistent with the known theoretical principles of liquid chromatography. Histograms of the effect of the retention time of standard sorbates on their nature and boiling point, where isopropanol and 2-ethoxyethanol are extreme, are presented. In this case, isopropanol having a lower boiling point than 2-Ethoxyethanol is retained on the sorbent more strongly, which is associated with the formation of intermolecular hydrogen bonds with surface silanol groups of the sorbent.